Dynamika analogii - Stanisław Buda (Zagadnienia Filozoficzne w Nauce, 2006)
The article deals with the simplest, least philosophically engaged, attempts to define analogy. The author is skeptical as far as the possibility of reducing analogy to the linguistic equipment of logic or of enclosing it in any formal schemes is concerned. Looking for the ontic basis of analogy, he shows its possible rooting in objects. In doing so he employs the notions of idea and model as defined by himself. He suggests an irreplaceable role of analogy in scientific reflection.